AN ANALYSIS OF âWORK OF MIRACLES IN HELEN KELLERâ FROM SOCIAL PERSPECTIVE AND MORAL VALUE - ., Ardayati (JURNAL SMART, 2016)
This study was carried out based on the problems faced by the writer as a English teacher. Most of students have no motivation when they found difficulties especially in learning English. Furthermore, the reasons why the researcher used The Miracle worker film to be investigated: Firstly, this movie was made based on the true story. Secondly, it transferred moral values. Thirdly, it told efforts of a teacher, Annie Sullivan. The research problems were âWhat are social perspective of Helen Keller and what are moral values found in The Miracle Worker film?â The study employed a qualitative research which was intended to analyze Helen Kellerâs social life, social life at the society illustrated in that movie, and moral values found in the movie. The research instrument was investigator triangulation which referred to the use of more than one audience in the field to gather and interpret data. In conclusion the Miracle Worker was an inspirational movie because it told about a blind deaf woman to reach her goals. It delivered Helen Kellerâs experience detailing her early life. Moral values of the film were motivation, kindness, responsibility, honestly, empathy, and respect.Key words: Social perspective, the Miracle worker, moral value